Spatial Distribution of High-Rise Buildings within Urban Areas: The Case of the Tel Aviv Metropolitan Region - Amnon Frenkel (European Regional Science Association (ERSA), 2004)
The spatial aspects of high-rise buildings in the Tel Aviv metropolitan region in Israel are examined, using empirical data gathered through a field survey. A multinomial logic model is employed to test the hypotheses concerning the cyclic model in the development of the metropolitan region. The results support empirical evidence of the dispersal of high-rise buildings in space, indicating an initial process of convergence in the Tel Aviv metropolitan pattern. The study points out that intensive high-rise building is expected to develop extensively in the future, particularly in the core and inner-ring cities. A classic negative gradient pattern is indicated in the dispersal of intensive high-rise building, moving from the core area toward the outskirts of the metropolitan region. In contrast, the classic pattern between center and fringes does not hold within the built-up areas of the cities.
Keywords: 330